Nailfold capillaroscopic changes in patients with idiopathic pulmonary arterial hypertension and systemic sclerosis-related pulmonary arterial hypertension - Corrado, A.; Correale, M.; Mansueto, N.; Monaco, I.; Carriero, A.; Mele, A.; Colia, R.; Di Biase, M.; Cantatore, F.P. (Microvascular research, 2017)
Pulmonary arterial hypertension (PAH) represents one of the main clinical expressions of the vascular changes in systemic sclerosis (SSc). Lung microvascular changes can play a role in the pathogenesis of idiopathic PAH (IPAH) also. The aim of this study is to investigate the presence of capillaroscopic abnormalities in patients with IPAH and to evaluate the differences in capillary nailfold changes between patients with IPAH and patients with SSc with and without PAH. 39 SSc patients (19 with PAH – SSc-PAH and 20 without – SSc-noPAH), 21 subjects with IPAH and 20 healthy subjects were recruited. PAH was diagnosed by right heart catheterization. Nailfold videocapillaroscopy was performed (NVC) in all recruited subjects; capillary quantitative parameters (loops length and width, capillary density, neoangiogenesis) were evaluated and a semiquantitative scoring was used (normal, minor or major abnormalities for healthy controls and IPAH subjects and specific patterns – early, active and late – for SSc subjects) to define microvascular alterations. The presence of capillaroscopic abnormalities was detected in 38,1% subjects with IPAH; particularly, compared to healthy controls, capillary density was significantly lower (7,5±1,65loops/mm vs 9±1,37loops/mm p<0,05) and mean capillary width was significantly higher (21±13μm vs 17±3μm p<0,05). A more severe NVC pattern (active/late) was described. SSc-PAH patients compared to SSc-noPAH patients (73,2% vs 50% respectively, p<0,05), with a significantly lower capillary density (5,64±1,9loops/mm vs 6,5±1,3loops/mm p<0,05) and a significantly higher capillary width (55±7μm vs 35±8μm - p<0,05) and mean number of neoangiogenesis (N/mm) (1±0,33 vs 0,2±0,22 respectively p<0,05). These data, beyond to confirm the role of microvascular damage in SSc-related PAH, support the hypothesis of systemic microvascular involvement in IPAH also, which can be detected by NVC, although further studies are needed to establish whether the changes in the systemic microcirculation are causal or consequential to PAH.